The Role of the Private Sector in Developing and Supporting International Competitiveness - Irina-Elena Gentimir (CES Working Papers, 2013)
In the actual context of economic globalization, the competitiveness has a crucial importance for all the countries. But due to which factors and to what extent takes place the creation and improvement of it? This paper traces the role of the private sector in creating and sustaining international competitiveness, it summarizes three determinants of international competitiveness (productivity, innovation and clusters) and traces their impact on it. The main argument of this paper is that these three determinants developed at the microeconomic level play an important role for country's competitiveness due to their creation as a result of quality activities which take place in firms. At the same time, they are goals for a firm in its pursue for high profits and efficiency.
Keywords: F00; O31; 330; international competitiveness; private sector; productivity; innovation; clusters Romania